ETHNOPHARMACOLOGICAL AND PHYTOCHEMICAL STUDY OF MAJOR SPECIES FROM LABIATAE FAMILY IN SAUDI ARABIA: A SYSTEMATIC REVIEW - AHMAD, FAZIL; KAMARAJ, BALU; MOHAMED, JAMAL MOIDEEN MUTHU; EBRAHIM, DOAA; AL HUMOUD, SHOUG YOUSIF; EL-SAGHEER, AIDA MOHAMMED; EMAM, AMINA SABRY ABDALGHAFFAR (International Journal of Applied Pharmaceutics, 2022)
A review on a medicinal plant belong to family Labiatae has been made in the Kingdom of Saudi Arabia. Among the reported flora in the Kingdom of Saudi Arabia, Labiatae family has the highest species. A total of 23 species of Labiatae family has been reported with high medicinal value. A detail review on 12 species of Labiatae family had done to know their phytochemical constituents, medicinal uses and pharmacological properties. In this review we also explore the total chemical constituents present in each plant with a unique list of 3D chemical structures. (E)-2-Hexenal, 1,8-Cineole, Bicyclogermacrene, Borneol, Bornyl acetate, Bulnesol, Caffeic acid, Camphene, Camphor, Eugenol, Gallic acid, Quercetin, Terpinene, Thymol, etc are the important constituent in these 12 species of Labiatae family. This study also shows that Marrubium vulgare L, Ocimum basilicum L, Origanum majorana and Otostegia fruticosa plants had reported with many medicinal uses and pharmacological properties. Medicinal constituents include the highest phenolic, flavonoid content and strong aromatic essential oil. Further scientific investigations on these 12 species are needed to explore toxicity and clinical efficacy and as well as to explore the therapeutic effects of major secondary metabolites. The summarized information from the current review may be a useful tool for researchers to carry out further study and explore other scientific aspects of the herbs.